A meta-study of qualitative research examining stressor appraisals and coping among adolescents in sport - Tamminen, K. A.; Holt, N. L. (Journal of Sports Sciences, 2010)
The main aim of this study was to create an integrated theoretical perspective of the qualitative adolescent sport stressor appraisal and coping literature. A secondary aim was to critique theoretical and methodological issues in the extant literature. Following database searches, 20 studies were retained for analysis. Meta-data, meta-theory, and meta-method analyses were conducted followed by a final meta-synthesis of findings. Analyses produced four themes: contextual and dynamic stressor appraisals, contextual and dynamic coping, coping resources and processes of acquisition, and social networks as assets and liabilities. Findings highlight the need for precise use of theory in the study of coping. Finally, while several data collection methods have been used, there is scope for greater methodological diversity to advance our understanding of coping among adolescent athletes.